Simultaneous MgO coating and Mg doping of Na[Ni0.5Mn0.5]O2 cathode: facile and customizable approach to high-voltage sodium-ion batteries. Issue 35 (28th August 2018) - Hwang, Jang-Yeon; Yu, Tae-Yeon; Sun, Yang-Kook
Abstract : Simultaneous surface MgO coating to bulk Mg doping of Na[Ni0.5 Mn0.5 ]O2 cathode produces great synergy in sodium-ion battery performances. Abstract : Herein, we report substantially improved high-voltage stability of Na[Ni0.5 Mn0.5 ]O2 as a cathode material due to a surface MgO coating and bulk Mg doping for high-voltage sodium-ion batteries, for the first time. The MgO coating layer effectively suppressed the unfavorable side reactions during cycling while the partial Mg doping into the bulk Ni sites improved the structural stability by moderating the extent of the irreversible multiphase transformation. As a result, the combination of a MgO coating with Mg doping provides enhanced electrochemical performance and structural stability of Na[Ni0.5 Mn0.5 ]O2 within the voltage range of 2.0–4.2 V. The material demonstrated a high specific capacity of 167 mA h g −1 at a 0.1C and excellent cycling stability and rate capability with 60% capacity retention at 10C ( vs. the initial capacity at 0.1C). The practical acceptability of the simultaneous MgO coating and Mg doping of the Na[Ni0.5 Mn0.5 ]O2 cathode was obviously verified using scaled-up pouch-type full cells with hard carbon anodes.